CRITICAL ANALYSIS OF THE INFLUENCE OF BOYS' LOVE FILMS ON GENERATION Z'S PERSPECTIVE REGARDING LGBT (LESBIAN, GAY, BISEXUAL, AND TRANSGENDER) - Iis Juniati; Dinda Citra Dewi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Boys' Love (BL) films serve as an effective medium for increasing tolerance and understanding towards the LGBT community. The current easy access through various digital media platforms is a supporting factor. The proliferation of BL content films has now "influenced" Generation Z, changing their perspective on LGBT (Lesbian, Gay, Bisexual, and Transgender) individuals. In Indonesia, given the socio-cultural context, many fans of BL films view them merely as a form of entertainment with no intention of openly supporting the LGBT community's existence. Interestingly, continuous consumption of BL content can lead to a shift in one's viewpoint. Generation Z's pro and contra perspectives pose a dilemma in society. While LGBT is still considered contrary to norms by most of the global community, tolerance for LGBT individuals is now emerging from Generation Z. The background for Generation Z's acceptance of LGBT stems from technological advancements and the effects of dissemination through social media. The authors will examine this phenomenon using critical discourse analysis and conduct interviews with Generation Z fans of Boys' Love films.